The Effect of Work System Optimization on the Efficiency and Productivity Assembly Workstation Product Using an Integrated TMS - Dony Susandi; Hafini Rizanuddin Nur; Intan Kusuma Dewi; Asri Nurhasanah (Universitas Suryakancana, 2026)
Productivity is an important aspect in the manufacturing industry, including in the assembly process of the Cover Seat Belt Anchor product at PT Solo Plastik Indonesia. Problems found include the absence of standard work methods, high variations in operator movements, and irregular process times that result in motion waste and fluctuating production achievements. This study aims to analyze the existing work system and develop proposals for improvement methods to increase efficiency and productivity. The methods used include Time and Motion Study (TMS), Value Stream Mapping (VSM), right-left hand maps, therblig analysis, motion economy principles, and stopwatch study. Data was obtained through direct observation, measurement of operator work time, and identification of motion elements. The results show that 5 ineffective motion elements can be eliminated or combined. The proposed work method can reduce standard time from 60 seconds to 48.83 seconds per unit (efficiency ±9.3%), balance the use of the right and left hands, and reduce motion waste. The implementation of standardized work methods has the potential to increase operator productivity and work quality, in line with the current trend in the automotive industry that integrates lean manufacturing and ergonomics.